Comparison between single-chamber and dual-chamber photocatalytic fuel cell on synthetic dye removal efficiency and power generation - Liu, Jia Chee; Antonio Choon Kiat, Niang; Tay, Meng Guan (John Wiley & Sons, Inc, 2025)
Photocatalytic fuel cell (PFC) is the combination of photocatalysis and fuel cell that can be used to treat wastewater and produce electrical energy simultaneously. Dual-chamber photocatalytic fuel cell (DCPFC) has been reported to have better performance than single-chamber photocatalytic fuel cell (SCPFC) because of the ability to prevent the electron-hole recombination in DCPFC. But there was not many side-by-side studies found in the literature to compare the performance in between SCPFC and DCPFC. This study presents a comprehensive comparison at different parameter between typical SCPFC and DCPFC for the synthetic methyl red dye degradation and power generation under different conditions. The performance of PFC influenced by the electron transfer driven by potential difference between two electrodes. SCPFC system suffers from the fast recombination of electron-hole pairs. In the present study, a DCPFC setup was setup by separating the photoanode and cathode into two different chambers to prevent the rapid electron-hole recombination. Both types of PFC used ZnO/Zn as photoanode to treat the 10 ppm synthetic methyl red dye solution at pH 4. The DCPFC achieved a highest power generation (130.24 mW/cm2) and 100% dye degradation, significantly outperforming than SCPFC which obtained the highest power generation (59.85 mW/cm2) and 12.23% dye degradation. The ZnO/Zn photoanode can be reused twice in DCPFC but only once in SCPFC. This study highlights the advantages of DCPFC in its’ performance and hence the design can be served as a model for the future reference. Indeed, the output of the research aligns with SDGs in clean water, clean energy, and life below water.